Creative greeting cards - Genovese, Sandi; Packham, Jo (Sterling : Orion New York, London, 2002)
In "Creative Greeting Cards," part of the Sandi Genovese Ellison series, readers discover innovative techniques for crafting personalized cards for any occasion. The book combines artistic inspiration with step-by-step instructions, making it accessible for crafters of all skill levels. With a focus on creativity and individuality, it encourages self-expression through handmade greetings.